Conductive ceramic material and preparation method thereof

By using specific raw materials and processes to prepare conductive composite ceramic materials, the problems of low conductivity and poor mechanical properties of existing ceramic materials are solved, and ceramic materials with high conductivity and high mechanical strength are achieved.

CN119409512BActive Publication Date: 2025-04-08SHANDONG XINJING CERAMIC NEW MATERIAL TECH DEV CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510027826.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-08
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

The low electrical conductivity and poor mechanical properties of existing ceramic materials limit the development of conductive ceramic materials.

Method used

The conductive composite ceramic material is prepared by using boron nitride powder, silicon carbide powder, titanium diboride powder and graphene as raw materials, and ultrasonic dispersion, ball milling treatment and hot pressing sintering.

Benefits of technology

Ceramic materials with high conductivity and high mechanical strength have good heat and impact resistance, and are suitable for high temperature and high strength environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure ELSAT9QIVX2OMVYZHESBQ2HEYA6CXJMTSHEWO4JJ
    Figure ELSAT9QIVX2OMVYZHESBQ2HEYA6CXJMTSHEWO4JJ
Patent Text Reader

Abstract

The present invention belongs to the technical field of ceramic materials, and specifically relates to a conductive ceramic material and a preparation method thereof. The present invention uses boron nitride powder, silicon carbide powder, titanium diboride powder, and graphene as raw materials, and prepares conductive composite ceramics through a hot pressing sintering process. The dispersibility and conductivity of the graphene material are improved by selecting graphene with a specific size and carbon-oxygen ratio. The appropriate carbon-oxygen ratio not only improves the dispersibility of graphene in the solvent and the ability to combine with ceramic powder, but also maintains the good mechanical properties of graphene, and prevents excessive oxygen-containing functional groups from damaging the graphene structure. This process emphasizes the in-situ compounding between the materials of each phase, blurs the phase boundaries between the materials of each phase, reflects the characteristics of the materials of each phase as much as possible, and obtains a conductive composite ceramic material with higher mechanical properties by sintering at a relatively low temperature through a traditional method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic materials, and in particular relates to a conductive ceramic material and a preparation method thereof. Background Art

[0002] Ceramic materials refer to the general term for all materials except metal materials and organic polymer materials, that is, inorganic non-metallic materials. For a long time, the development of ceramic materials has mainly relied on the inheritance of craftsmanship, and its products are mainly daily utensils, building materials, etc., which are usually called traditional ceramics. With the rise of new technologies, such as space technology, laser technology, electronic technology, computer technology, and the development of basic theoretical research and testing technology, the research on ceramic materials has also made rapid progress, resulting in the emergence of many ceramics with different characteristics, such as high-temperature structural ceramics, piezoelectric ceramics, photosensitive ceramics, etc. These newly developed ceramics are very different from traditional ceramics in terms of performance, raw materials or technology. In order to distinguish them from traditional ceramics, these ceramics are called special ceramics or advanced ceramics. In terms of function, special ceramics have special properties that traditional ceramics do not have, such as high strength, high hardness, corrosion resistance, and unique properties in sound, light, electricity, magnetism, heat, etc. Therefore, special ceramics are widely used in high temperature, electronics, energy, machinery, aerospace and other fields; in terms of raw materials, traditional ceramics mainly use clay as raw material, while the main raw materials of special ceramics are oxides, carbides, nitrides, silicides, etc.; in terms of preparation technology, special ceramics are not only produced in traditional furnaces, but also widely use discharge plasma sintering, vacuum sintering, protective atmosphere sintering, hot pressing sintering, hot isostatic pressing sintering and other means.

[0003] Special ceramics can be divided into structural ceramics and functional ceramics according to their different uses. Structural ceramic materials have good mechanical properties and are often used as engineering structural parts to exert mechanical efficiency. They have the characteristics of high strength, high hardness, high temperature resistance, corrosion resistance, and wear resistance. They are mainly used in automobiles, aircraft, rockets, etc. With the vigorous development of modern industries such as aviation, aerospace, and advanced energy, the requirements for high-temperature and high-strength materials are becoming more and more stringent, and the performance of metal-based high-temperature alloys is often difficult to meet the requirements. Compared with metal materials, special ceramic materials have a high melting point temperature and excellent chemical stability, oxidation resistance and other excellent properties, so special ceramics are increasingly used in the field of high-temperature technology.

[0004] Functional ceramics refer to ceramic materials that are mainly used for their non-mechanical properties. Such materials often have one or more functions, such as electrical, magnetic, acoustic, optical, thermal, chemical, biological or their coupled functions. The most common functional materials are electromagnetic functional materials, which mainly include device ceramics (electrical insulation ceramics), capacitor ceramics, piezoelectric ceramics, magnetic ceramics, conductive ceramics, superconducting ceramics, semiconductor ceramics, etc.

[0005] Conductive ceramics and superconducting ceramics are ceramics that work by using the conductivity of ceramics. Semiconductor ceramics are key materials for sensor technology and sensitive components, and are mainly divided into thermistors, photoresistors, semiconductor ceramic capacitors, humidity sensors, gas sensors, etc. Among them, conductive ceramics have the characteristics of good conductivity, high strength, good chemical stability, corrosion resistance, high temperature resistance, wear resistance, etc., and have both the excellent mechanical properties of ceramic materials and the conductive properties of metal-like materials. They can be used in many special occasions and environments. Therefore, the research on conductive ceramics has received people's attention and its application has become more and more extensive. At present, the research on conductive ceramics at home and abroad is mainly focused on multiphase conductive ceramics. Multiphase conductive ceramics are ceramic materials that add conductive phases to the matrix to make the material have conductive properties. With the continuous expansion and popularization of the application of functional materials, the application field of conductive ceramics is also expanding. It is a functional material with broad application prospects. However, the current ceramic materials have low conductivity and poor mechanical properties, which limits the development of conductive ceramic materials. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a conductive ceramic material, which has the advantages of high conductivity and high mechanical strength.

[0007] The present invention is achieved through the following technical solutions:

[0008] A method for preparing a conductive ceramic material comprises the following steps:

[0009] (1) Weigh 70-80 parts of boron nitride powder, 10-20 parts of silicon carbide powder, 3-6 parts of titanium diboride powder, and 0.5-2 parts of graphene by weight; wherein the lateral size of the graphene is 1-10 μm; and the carbon-oxygen ratio is (30-50):1;

[0010] (2) ultrasonically dispersing graphene in an alcohol solvent to obtain a graphene dispersion;

[0011] (3) adding boron nitride powder, silicon carbide powder and titanium diboride powder to the graphene dispersion and stirring evenly to obtain a mixed solution;

[0012] (4) ball-milling the mixed solution, drying it, and sieving it to obtain a mixed powder;

[0013] (5) The mixed powder is placed in a hot press furnace and sintered to obtain a conductive ceramic material.

[0014] Conductive composite ceramics are required to have appropriate resistivity, excellent heat resistance and impact resistance, as well as sufficiently high mechanical strength. Conductive composite ceramics containing BN are a viable option, and TiB2 can be selected as the conductive phase. TiB2 has a high melting point, high chemical stability (corrosion resistance and oxidation resistance), high hardness, excellent wear resistance and good thermal conductivity. The most prominent advantage of TiB2 is its good electrical conductivity, metal-like electronic conductivity and positive resistivity temperature coefficient. At room temperature, its resistivity is almost comparable to that of Cu. However, attention should be paid to the amount of TiB2 used. When the amount of TiB2 is too much, agglomeration may occur and cause abnormal growth of grains, resulting in reduced mechanical properties of ceramic composite materials.

[0015] However, the mechanical properties and electrical conductivity of simple TiB2-BN conductive composite ceramics still cannot meet the use requirements of high-conductivity ceramics. Therefore, the present invention has added SiC ceramic material and graphene conductive material. The addition of SiC ceramic material can obtain finer grains, which is conducive to the improvement of material strength. By adding multiphase particles, certain plastic deformation is produced under external force or creep is produced along the crystal interface slip to relieve stress concentration, and the effect of strengthening toughening is achieved. In addition, the difference in elastic modulus and expansion coefficient between the SiC two-phase particles with high melting point and high hardness and the matrix grains forms a residual stress field around the particles and the matrix during cooling, and the interaction of this stress field and the extended crack tip stress can produce crack deflection, detour, branching and pinning effects, which play a toughening effect on the matrix.

[0016] Graphene is a typical two-dimensional material. In one dimension, the material size is reduced to the thickness of several or even a single atom, while in the other two dimensions, the relative size is larger. The addition of graphene can significantly improve the toughness of ceramic materials, while graphene has good electrical and thermal conductivity. However, it is difficult to efficiently prepare graphene-ceramic composite powders due to the poor dispersibility of graphene in solvents and ceramic materials, or the need to use a large amount of organic solvents or dispersants; and the preparation process of graphene oxide has safety issues, and the performance of graphene oxide is significantly lower than that of graphene, thus restricting the overall performance improvement of composite ceramics; although the reduced graphene oxide-ceramic composite material is superior to graphene oxide in performance, the structure and performance of graphene caused by the oxidation-reduction process are still irreversible. Therefore, the present invention improves the dispersibility and electrical conductivity of graphene materials by selecting graphene with a specific size and carbon-oxygen ratio. The appropriate carbon-oxygen ratio not only improves the dispersibility of graphene in solvents and the ability to combine with ceramic powders, but also maintains the good mechanical properties of graphene, preventing the destruction of the graphene structure by too many oxygen-containing functional groups. If the carbon-oxygen ratio is too high, the graphene surface will contain fewer oxygen-active groups, the dispersion will be poor, and it will be difficult to build a conductive network; if the carbon-oxygen ratio is too low, the complete structure of graphene will be destroyed, the conductivity and mechanical properties will be reduced, which is not conducive to improving the mechanical properties and conductive properties of ceramics.

[0017] Furthermore, the boron nitride is hexagonal boron nitride; the titanium diboride is hexagonal titanium diboride; and the silicon carbide is face-centered cubic silicon carbide.

[0018] Furthermore, in step (1), the average particle size of the boron nitride powder is (D50) 0.5-1 μm, the average particle size of the silicon carbide powder is (D50) 0.5-1 μm, and the average particle size of the titanium diboride powder is (D50) 1-3 μm.

[0019] Furthermore, in step (1), the lateral size of graphene is 3-6 μm. The appropriate particle size is not only conducive to the uniform distribution of graphene in the sample, promoting the formation of a conductive network and improving the conductive performance, but also can promote the densification process of the green body in the middle and late stages of sintering, improving the density and mechanical properties of the sample.

[0020] Furthermore, in step (2), the alcohol solvent is at least one of methanol, ethanol, propanol, ethylene glycol and propylene glycol.

[0021] Furthermore, the power of ultrasonic dispersion in step (2) is 100-200W.

[0022] Furthermore, in step (3), the stirring rate is 100-300 rpm.

[0023] Furthermore, in step (4), the ball-to-material ratio of the ball milling process is (4-6): 1, the ball milling speed is 200-400 rpm, and the ball milling time is 2-4 h.

[0024] Furthermore, in step (5), the hot pressing pressure is 30-40 MPa, the sintering heating rate is 80-110°C / min, the sintering temperature is 1800-1950°C, and the sintering time is 1.5-2h. Furthermore, the sintering temperature is 1870-1920°C.

[0025] Furthermore, 13-16 parts of silicon carbide powder. SiC is an ideal additive for BN. Due to its excellent characteristics of high hardness, SiC can be introduced into BN to maintain the hardness of BN to a large extent, and at the same time can improve the sintering performance and mechanical properties of BN. Since Si is close to B in the periodic table, they have similar properties. According to the principle of similar compatibility, SiC is easily dissolved in BN to form a solid solution, thereby reducing the grain boundary energy of BN and promoting the densification of the material. However, excessive SiC is prone to agglomeration, resulting in defects and the formation of tiny pores, which may lead to a decrease in mechanical properties.

[0026] On the other hand, the present invention also provides a conductive ceramic material. The graphene-enhanced composite ceramic can maintain the excellent properties shared by both carbon materials and ceramic materials, and has the characteristics of conductivity, impact resistance, machinability, corrosion resistance, etc., and has broad application prospects in the conductive ceramic industry.

[0027] Beneficial effects: Conductive composite ceramics are an important development direction of advanced structural materials. Based on the research of single-phase materials, the synergistic effect caused by the interaction of multiple strengthening mechanisms is used to perform multi-level composites on ceramic materials to obtain super-strong and super-tough high-performance conductive ceramics. The present invention uses boron nitride powder, silicon carbide powder, titanium diboride powder, and graphene as raw materials, and prepares conductive composite ceramics through conventional hot pressing and sintering processes. The dispersibility and conductivity of graphene materials are improved by selecting graphene with a specific size and carbon-oxygen ratio. The appropriate carbon-oxygen ratio not only improves the dispersibility of graphene in the solvent and its ability to bind to ceramic powder, but also maintains the good mechanical properties of graphene, and prevents excessive oxygen-containing functional groups from damaging the graphene structure. This process emphasizes the in-situ composite between the materials of each phase, blurs the phase boundaries between the materials of each phase, reflects the characteristics of the materials of each phase as much as possible, and obtains a dense composite ceramic material by sintering in a traditional way at a lower temperature. DETAILED DESCRIPTION

[0028] The above scheme is further described below in conjunction with specific embodiments; it should be understood that these embodiments are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following embodiments; the implementation conditions adopted in the embodiments can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions in conventional experiments.

[0029] Example 1

[0030] A method for preparing a conductive ceramic material comprises the following steps:

[0031] (1) Weigh 70 parts of boron nitride powder, 13 parts of silicon carbide powder, 3 parts of titanium diboride powder, and 0.5 parts of graphene by weight; wherein the lateral size of graphene is 3 μm; the carbon-oxygen ratio is 30:1; the average particle size of the boron nitride powder is 0.8 μm, the average particle size of the silicon carbide powder is 0.7 μm, and the average particle size of the titanium diboride powder is 1.8 μm;

[0032] (2) ultrasonically dispersing graphene in an ethanol solvent to obtain a graphene dispersion; the power of the ultrasonic dispersion is 100 W;

[0033] (3) Adding boron nitride powder, silicon carbide powder and titanium diboride powder to the graphene dispersion and stirring evenly to obtain a mixed solution; the stirring rate is 100 rpm;

[0034] (4) ball milling the mixed solution, drying it, and sieving it to obtain a mixed powder; the ball-to-material ratio of the ball milling process is 5:1, the ball milling speed is 200 rpm, and the ball milling time is 4 h;

[0035] (5) The mixed powder is placed in a hot pressing furnace and sintered to obtain a conductive ceramic material; the hot pressing pressure is 30 MPa; the sintering heating rate is 80°C / min, the sintering temperature is 1920°C, and the sintering time is 1.5 h.

[0036] Example 2

[0037] A method for preparing a conductive ceramic material comprises the following steps:

[0038] (1) Weigh 80 parts of boron nitride powder, 16 parts of silicon carbide powder, 6 parts of titanium diboride powder, and 2 parts of graphene by weight; wherein the lateral size of graphene is 6 μm; the carbon-oxygen ratio is 50:1; the average particle size of the boron nitride powder is 0.8 μm, the average particle size of the silicon carbide powder is 0.7 μm, and the average particle size of the titanium diboride powder is 1.8 μm;

[0039] (2) ultrasonically dispersing graphene in an ethanol solvent to obtain a graphene dispersion; the power of the ultrasonic dispersion is 200 W;

[0040] (3) Adding boron nitride powder, silicon carbide powder and titanium diboride powder to the graphene dispersion and stirring evenly to obtain a mixed solution; the stirring rate is 300 rpm;

[0041] (4) ball milling the mixed solution, drying it, and sieving it to obtain a mixed powder; the ball-to-material ratio of the ball milling process is 5:1, the ball milling speed is 400 rpm, and the ball milling time is 2 h;

[0042] (5) The mixed powder is placed in a hot pressing furnace and sintered to obtain a conductive ceramic material; the hot pressing pressure is 40 MPa; the sintering heating rate is 110°C / min, the sintering temperature is 1870°C, and the sintering time is 2 h.

[0043] Example 3

[0044] A method for preparing a conductive ceramic material comprises the following steps:

[0045] (1) Weigh 70 parts of boron nitride powder, 16 parts of silicon carbide powder, 3 parts of titanium diboride powder, and 2 parts of graphene by weight; wherein the lateral size of graphene is 3 μm; the carbon-oxygen ratio is 50:1; the average particle size of the boron nitride powder is 0.8 μm, the average particle size of the silicon carbide powder is 0.7 μm, and the average particle size of the titanium diboride powder is 1.8 μm;

[0046] (2) ultrasonically dispersing graphene in an ethanol solvent to obtain a graphene dispersion; the power of the ultrasonic dispersion is 100 W;

[0047] (3) Adding boron nitride powder, silicon carbide powder and titanium diboride powder to the graphene dispersion and stirring evenly to obtain a mixed solution; the stirring rate is 300 rpm;

[0048] (4) ball milling the mixed solution, drying it, and sieving it to obtain a mixed powder; the ball-to-material ratio of the ball milling process is 5:1, the ball milling speed is 200 rpm, and the ball milling time is 2 h;

[0049] (5) The mixed powder is placed in a hot pressing furnace and sintered to obtain a conductive ceramic material; the hot pressing pressure is 40 MPa; the sintering heating rate is 80°C / min, the sintering temperature is 1920°C, and the sintering time is 2 h.

[0050] Example 4

[0051] A method for preparing a conductive ceramic material comprises the following steps:

[0052] (1) Weigh 73 parts of boron nitride powder, 14 parts of silicon carbide powder, 3.5 parts of titanium diboride powder, and 0.8 parts of graphene by weight; wherein the lateral size of graphene is 4 μm; the carbon-oxygen ratio is 35:1; the average particle size of boron nitride powder is 0.8 μm, the average particle size of silicon carbide powder is 0.7 μm, and the average particle size of titanium diboride powder is 1.8 μm;

[0053] (2) ultrasonically dispersing graphene in an ethanol solvent to obtain a graphene dispersion; the power of the ultrasonic dispersion is 130 W;

[0054] (3) Adding boron nitride powder, silicon carbide powder and titanium diboride powder to the graphene dispersion and stirring evenly to obtain a mixed solution; the stirring rate is 160 rpm;

[0055] (4) ball milling the mixed solution, drying it, and sieving it to obtain a mixed powder; the ball-to-material ratio of the ball milling process is 5:1, the ball milling speed is 250 rpm, and the ball milling time is 3.5 h;

[0056] (5) The mixed powder is placed in a hot pressing furnace and sintered to obtain a conductive ceramic material; the hot pressing pressure is 35 MPa; the sintering heating rate is 90°C / min, the sintering temperature is 1880°C, and the sintering time is 1.9 h.

[0057] Example 5

[0058] A method for preparing a conductive ceramic material comprises the following steps:

[0059] (1) Weigh 77 parts of boron nitride powder, 15 parts of silicon carbide powder, 5.6 parts of titanium diboride powder, and 1.7 parts of graphene by weight; wherein the lateral size of graphene is 5 μm; the carbon-oxygen ratio is 45:1; the average particle size of the boron nitride powder is 0.8 μm, the average particle size of the silicon carbide powder is 0.7 μm, and the average particle size of the titanium diboride powder is 1.8 μm;

[0060] (2) ultrasonically dispersing graphene in an ethanol solvent to obtain a graphene dispersion; the power of the ultrasonic dispersion is 180 W;

[0061] (3) Adding boron nitride powder, silicon carbide powder and titanium diboride powder to the graphene dispersion and stirring evenly to obtain a mixed solution; the stirring rate is 250 rpm;

[0062] (4) ball milling the mixed solution, drying it, and sieving it to obtain a mixed powder; the ball-to-material ratio of the ball milling process is 5:1, the ball milling speed is 350 rpm, and the ball milling time is 2.5 h;

[0063] (5) The mixed powder is placed in a hot pressing furnace and sintered to obtain a conductive ceramic material; the hot pressing pressure is 38 MPa; the sintering heating rate is 100°C / min, the sintering temperature is 1910°C, and the sintering time is 1.6 h.

[0064] Example 6

[0065] A method for preparing a conductive ceramic material comprises the following steps:

[0066] (1) Weigh 75 parts of boron nitride powder, 10 parts of silicon carbide powder, 4 parts of titanium diboride powder, and 1.2 parts of graphene by weight; wherein the lateral size of graphene is 4 μm; the carbon-oxygen ratio is 40:1; the average particle size of boron nitride powder is 0.8 μm, the average particle size of silicon carbide powder is 0.7 μm, and the average particle size of titanium diboride powder is 1.8 μm;

[0067] (2) ultrasonically dispersing graphene in an ethanol solvent to obtain a graphene dispersion; the power of the ultrasonic dispersion is 150 W;

[0068] (3) Adding boron nitride powder, silicon carbide powder and titanium diboride powder to the graphene dispersion and stirring evenly to obtain a mixed solution; the stirring rate is 200 rpm;

[0069] (4) ball milling the mixed solution, drying it, and sieving it to obtain a mixed powder; the ball-to-material ratio of the ball milling process is 5:1, the ball milling speed is 300 rpm, and the ball milling time is 3 h;

[0070] (5) The mixed powder is placed in a hot pressing furnace and sintered to obtain a conductive ceramic material; the hot pressing pressure is 35 MPa; the sintering heating rate is 100°C / min, the sintering temperature is 1900°C, and the sintering time is 1.8 h.

[0071] Example 7

[0072] A method for preparing a conductive ceramic material comprises the following steps:

[0073] (1) Weigh 75 parts of boron nitride powder, 20 parts of silicon carbide powder, 4 parts of titanium diboride powder, and 1.2 parts of graphene by weight; wherein the lateral size of graphene is 4 μm; the carbon-oxygen ratio is 40:1; the average particle size of boron nitride powder is 0.8 μm, the average particle size of silicon carbide powder is 0.7 μm, and the average particle size of titanium diboride powder is 1.8 μm;

[0074] (2) ultrasonically dispersing graphene in an ethanol solvent to obtain a graphene dispersion; the power of the ultrasonic dispersion is 150 W;

[0075] (3) Adding boron nitride powder, silicon carbide powder and titanium diboride powder to the graphene dispersion and stirring evenly to obtain a mixed solution; the stirring rate is 200 rpm;

[0076] (4) ball milling the mixed solution, drying it, and sieving it to obtain a mixed powder; the ball-to-material ratio of the ball milling process is 5:1, the ball milling speed is 300 rpm, and the ball milling time is 3 h;

[0077] (5) The mixed powder is placed in a hot pressing furnace and sintered to obtain a conductive ceramic material; the hot pressing pressure is 35 MPa; the sintering heating rate is 100°C / min, the sintering temperature is 1900°C, and the sintering time is 1.8 h.

[0078] Example 8

[0079] A method for preparing a conductive ceramic material comprises the following steps:

[0080] (1) Weigh 75 parts of boron nitride powder, 15 parts of silicon carbide powder, 4 parts of titanium diboride powder, and 1.2 parts of graphene by weight; wherein the lateral size of graphene is 1 μm; the carbon-oxygen ratio is 40:1; the average particle size of boron nitride powder is 0.8 μm, the average particle size of silicon carbide powder is 0.7 μm, and the average particle size of titanium diboride powder is 1.8 μm;

[0081] (2) ultrasonically dispersing graphene in an ethanol solvent to obtain a graphene dispersion; the power of the ultrasonic dispersion is 150 W;

[0082] (3) Adding boron nitride powder, silicon carbide powder and titanium diboride powder to the graphene dispersion and stirring evenly to obtain a mixed solution; the stirring rate is 200 rpm;

[0083] (4) ball milling the mixed solution, drying it, and sieving it to obtain a mixed powder; the ball-to-material ratio of the ball milling process is 5:1, the ball milling speed is 300 rpm, and the ball milling time is 3 h;

[0084] (5) The mixed powder is placed in a hot pressing furnace and sintered to obtain a conductive ceramic material; the hot pressing pressure is 35 MPa; the sintering heating rate is 100°C / min, the sintering temperature is 1900°C, and the sintering time is 1.8 h.

[0085] Example 9

[0086] A method for preparing a conductive ceramic material comprises the following steps:

[0087] (1) Weigh 75 parts of boron nitride powder, 15 parts of silicon carbide powder, 4 parts of titanium diboride powder, and 1.2 parts of graphene by weight; wherein the lateral size of graphene is 10 μm; the carbon-oxygen ratio is 40:1; the average particle size of boron nitride powder is 0.8 μm, the average particle size of silicon carbide powder is 0.7 μm, and the average particle size of titanium diboride powder is 1.8 μm;

[0088] (2) ultrasonically dispersing graphene in an ethanol solvent to obtain a graphene dispersion; the power of the ultrasonic dispersion is 150 W;

[0089] (3) Adding boron nitride powder, silicon carbide powder and titanium diboride powder to the graphene dispersion and stirring evenly to obtain a mixed solution; the stirring rate is 200 rpm;

[0090] (4) ball milling the mixed solution, drying it, and sieving it to obtain a mixed powder; the ball-to-material ratio of the ball milling process is 5:1, the ball milling speed is 300 rpm, and the ball milling time is 3 h;

[0091] (5) The mixed powder is placed in a hot pressing furnace and sintered to obtain a conductive ceramic material; the hot pressing pressure is 35 MPa; the sintering heating rate is 100°C / min, the sintering temperature is 1900°C, and the sintering time is 1.8 h.

[0092] Example 10

[0093] A method for preparing a conductive ceramic material comprises the following steps:

[0094] (1) Weigh 75 parts of boron nitride powder, 15 parts of silicon carbide powder, 4 parts of titanium diboride powder, and 1.2 parts of graphene by weight; wherein the lateral size of graphene is 4 μm; the carbon-oxygen ratio is 40:1; the average particle size of boron nitride powder is 0.8 μm, the average particle size of silicon carbide powder is 0.7 μm, and the average particle size of titanium diboride powder is 1.8 μm;

[0095] (2) ultrasonically dispersing graphene in an ethanol solvent to obtain a graphene dispersion; the power of the ultrasonic dispersion is 150 W;

[0096] (3) Adding boron nitride powder, silicon carbide powder and titanium diboride powder to the graphene dispersion and stirring evenly to obtain a mixed solution; the stirring rate is 200 rpm;

[0097] (4) ball milling the mixed solution, drying it, and sieving it to obtain a mixed powder; the ball-to-material ratio of the ball milling process is 5:1, the ball milling speed is 300 rpm, and the ball milling time is 3 h;

[0098] (5) The mixed powder is placed in a hot pressing furnace and sintered to obtain a conductive ceramic material; the hot pressing pressure is 35 MPa; the sintering heating rate is 100°C / min, the sintering temperature is 1800°C, and the sintering time is 1.8 h.

[0099] Embodiment 11

[0100] A method for preparing a conductive ceramic material comprises the following steps:

[0101] (1) Weigh 75 parts of boron nitride powder, 15 parts of silicon carbide powder, 4 parts of titanium diboride powder, and 1.2 parts of graphene by weight; wherein the lateral size of graphene is 4 μm; the carbon-oxygen ratio is 40:1; the average particle size of boron nitride powder is 0.8 μm, the average particle size of silicon carbide powder is 0.7 μm, and the average particle size of titanium diboride powder is 1.8 μm;

[0102] (2) ultrasonically dispersing graphene in an ethanol solvent to obtain a graphene dispersion; the power of the ultrasonic dispersion is 150 W;

[0103] (3) Adding boron nitride powder, silicon carbide powder and titanium diboride powder to the graphene dispersion and stirring evenly to obtain a mixed solution; the stirring rate is 200 rpm;

[0104] (4) ball milling the mixed solution, drying it, and sieving it to obtain a mixed powder; the ball-to-material ratio of the ball milling process is 5:1, the ball milling speed is 300 rpm, and the ball milling time is 3 h;

[0105] (5) The mixed powder is placed in a hot pressing furnace and sintered to obtain a conductive ceramic material; the hot pressing pressure is 35 MPa; the sintering heating rate is 100°C / min, the sintering temperature is 1950°C, and the sintering time is 1.8 h.

[0106] Example 12

[0107] A method for preparing a conductive ceramic material comprises the following steps:

[0108] (1) Weigh 75 parts of boron nitride powder, 15 parts of silicon carbide powder, 4 parts of titanium diboride powder, and 1.2 parts of graphene by weight; wherein the lateral size of graphene is 4 μm; the carbon-oxygen ratio is 40:1; the average particle size of boron nitride powder is 0.8 μm, the average particle size of silicon carbide powder is 0.7 μm, and the average particle size of titanium diboride powder is 1.8 μm;

[0109] (2) ultrasonically dispersing graphene in an ethanol solvent to obtain a graphene dispersion; the power of the ultrasonic dispersion is 150 W;

[0110] (3) Adding boron nitride powder, silicon carbide powder and titanium diboride powder to the graphene dispersion and stirring evenly to obtain a mixed solution; the stirring rate is 200 rpm;

[0111] (4) ball milling the mixed solution, drying it, and sieving it to obtain a mixed powder; the ball-to-material ratio of the ball milling process is 5:1, the ball milling speed is 300 rpm, and the ball milling time is 3 h;

[0112] (5) The mixed powder is placed in a hot pressing furnace and sintered to obtain a conductive ceramic material; the hot pressing pressure is 35 MPa; the sintering heating rate is 100°C / min, the sintering temperature is 1900°C, and the sintering time is 1.8 h.

[0113] Comparative Example 1

[0114] A method for preparing a conductive ceramic material comprises the following steps:

[0115] (1) Weigh 75 parts of boron nitride powder, 15 parts of silicon carbide powder, 4 parts of titanium diboride powder, and 1.2 parts of graphene by weight; wherein the lateral size of graphene is 4 μm; the carbon-oxygen ratio is 20:1; the average particle size of boron nitride powder is 0.8 μm, the average particle size of silicon carbide powder is 0.7 μm, and the average particle size of titanium diboride powder is 1.8 μm;

[0116] (2) ultrasonically dispersing graphene in an ethanol solvent to obtain a graphene dispersion; the power of the ultrasonic dispersion is 150 W;

[0117] (3) Adding boron nitride powder, silicon carbide powder and titanium diboride powder to the graphene dispersion and stirring evenly to obtain a mixed solution; the stirring rate is 200 rpm;

[0118] (4) ball milling the mixed solution, drying it, and sieving it to obtain a mixed powder; the ball-to-material ratio of the ball milling process is 5:1, the ball milling speed is 300 rpm, and the ball milling time is 3 h;

[0119] (5) The mixed powder is placed in a hot pressing furnace and sintered to obtain a conductive ceramic material; the hot pressing pressure is 35 MPa; the sintering heating rate is 100°C / min, the sintering temperature is 1900°C, and the sintering time is 1.8 h.

[0120] Comparative Example 2

[0121] A method for preparing a conductive ceramic material comprises the following steps:

[0122] (1) Weigh 75 parts of boron nitride powder, 15 parts of silicon carbide powder, 4 parts of titanium diboride powder, and 1.2 parts of graphene by weight; wherein the lateral size of graphene is 4 μm; the carbon-oxygen ratio is 60:1; the average particle size of the boron nitride powder is 0.8 μm, the average particle size of the silicon carbide powder is 0.7 μm, and the average particle size of the titanium diboride powder is 1.8 μm;

[0123] (2) ultrasonically dispersing graphene in an ethanol solvent to obtain a graphene dispersion; the power of the ultrasonic dispersion is 150 W;

[0124] (3) Adding boron nitride powder, silicon carbide powder and titanium diboride powder to the graphene dispersion and stirring evenly to obtain a mixed solution; the stirring rate is 200 rpm;

[0125] (4) ball milling the mixed solution, drying it, and sieving it to obtain a mixed powder; the ball-to-material ratio of the ball milling process is 5:1, the ball milling speed is 300 rpm, and the ball milling time is 3 h;

[0126] (5) The mixed powder is placed in a hot pressing furnace and sintered to obtain a conductive ceramic material; the hot pressing pressure is 35 MPa; the sintering heating rate is 100°C / min, the sintering temperature is 1900°C, and the sintering time is 1.8 h.

[0127] Comparative Example 3

[0128] A method for preparing a conductive ceramic material comprises the following steps:

[0129] (1) Weigh 75 parts of boron nitride powder, 15 parts of silicon carbide powder, 4 parts of titanium diboride powder, and 0.2 parts of graphene by weight; wherein the lateral size of graphene is 4 μm; the carbon-oxygen ratio is 40:1; the average particle size of boron nitride powder is 0.8 μm, the average particle size of silicon carbide powder is 0.7 μm, and the average particle size of titanium diboride powder is 1.8 μm;

[0130] (2) ultrasonically dispersing graphene in an ethanol solvent to obtain a graphene dispersion; the power of the ultrasonic dispersion is 150 W;

[0131] (3) Adding boron nitride powder, silicon carbide powder and titanium diboride powder to the graphene dispersion and stirring evenly to obtain a mixed solution; the stirring rate is 200 rpm;

[0132] (4) ball milling the mixed solution, drying it, and sieving it to obtain a mixed powder; the ball-to-material ratio of the ball milling process is 5:1, the ball milling speed is 300 rpm, and the ball milling time is 3 h;

[0133] (5) The mixed powder is placed in a hot pressing furnace and sintered to obtain a conductive ceramic material; the hot pressing pressure is 35 MPa; the sintering heating rate is 100°C / min, the sintering temperature is 1900°C, and the sintering time is 1.8 h.

[0134] Comparative Example 4

[0135] A method for preparing a conductive ceramic material comprises the following steps:

[0136] (1) Weigh 75 parts of boron nitride powder, 15 parts of silicon carbide powder, 4 parts of titanium diboride powder, and 3 parts of graphene by weight; wherein the lateral size of graphene is 4 μm; the carbon-oxygen ratio is 40:1; the average particle size of the boron nitride powder is 0.8 μm, the average particle size of the silicon carbide powder is 0.7 μm, and the average particle size of the titanium diboride powder is 1.8 μm;

[0137] (2) ultrasonically dispersing graphene in an ethanol solvent to obtain a graphene dispersion; the power of the ultrasonic dispersion is 150 W;

[0138] (3) Adding boron nitride powder, silicon carbide powder and titanium diboride powder to the graphene dispersion and stirring evenly to obtain a mixed solution; the stirring rate is 200 rpm;

[0139] (4) ball milling the mixed solution, drying it, and sieving it to obtain a mixed powder; the ball-to-material ratio of the ball milling process is 5:1, the ball milling speed is 300 rpm, and the ball milling time is 3 h;

[0140] (5) The mixed powder is placed in a hot pressing furnace and sintered to obtain a conductive ceramic material; the hot pressing pressure is 35 MPa; the sintering heating rate is 100°C / min, the sintering temperature is 1900°C, and the sintering time is 1.8 h.

[0141] Comparative Example 5

[0142] A method for preparing a conductive ceramic material comprises the following steps:

[0143] (1) Weigh 75 parts of boron nitride powder, 15 parts of silicon carbide powder, 9 parts of titanium diboride powder, and 1.2 parts of graphene by weight; wherein the lateral size of graphene is 4 μm; the carbon-oxygen ratio is 40:1; the average particle size of the boron nitride powder is 0.8 μm, the average particle size of the silicon carbide powder is 0.7 μm, and the average particle size of the titanium diboride powder is 1.8 μm;

[0144] (2) ultrasonically dispersing graphene in an ethanol solvent to obtain a graphene dispersion; the power of the ultrasonic dispersion is 150 W;

[0145] (3) Adding boron nitride powder, silicon carbide powder and titanium diboride powder to the graphene dispersion and stirring evenly to obtain a mixed solution; the stirring rate is 200 rpm;

[0146] (4) ball milling the mixed solution, drying it, and sieving it to obtain a mixed powder; the ball-to-material ratio of the ball milling process is 5:1, the ball milling speed is 300 rpm, and the ball milling time is 3 h;

[0147] (5) The mixed powder is placed in a hot pressing furnace and sintered to obtain a conductive ceramic material; the hot pressing pressure is 35 MPa; the sintering heating rate is 100°C / min, the sintering temperature is 1900°C, and the sintering time is 1.8 h.

[0148] Performance test: The fracture toughness of the conductive ceramic materials prepared in Examples 1-12 and Comparative Examples 1-5 was tested by the single edge notched beam (SEBN) method; the resistivity of the conductive ceramic materials prepared in Examples 1-12 and Comparative Examples 1-5 was tested by the four-probe method. The results are shown in Table 1:

[0149]

[0150] As can be seen from Table 1, the present invention uses boron nitride powder, silicon carbide powder, titanium diboride powder, and graphene as raw materials, and prepares conductive multiphase ceramics through conventional hot pressing and sintering processes. The dispersibility and conductivity of graphene materials are improved by selecting graphene with a specific size and carbon-oxygen ratio. The appropriate carbon-oxygen ratio not only improves the dispersibility of graphene in solvents and the ability to bind with ceramic powders, but also maintains the good mechanical properties of graphene, and prevents the destruction of the graphene structure by too many oxygen-containing functional groups. This process emphasizes the in-situ compounding between the materials of each phase, blurs the phase boundaries between the materials of each phase, reflects the characteristics of the materials of each phase as much as possible, and obtains a dense multiphase ceramic material by sintering in a traditional manner at a lower temperature. Compared with Example 12, the carbon-oxygen ratio of graphene used in Comparative Example 1 is too low, the complete structure of graphene is destroyed, the conductivity and mechanical properties are reduced, and it is not conducive to the improvement of the mechanical properties and conductivity of ceramics; the carbon-oxygen ratio of graphene used in Comparative Example 2 is too high, the oxygen-containing active groups on the surface of graphene are less, the dispersibility is poor, and it is difficult to construct a conductive network. Comparative Examples 3-4 show that when the amount of graphene is too little, the conductive network cannot be limitedly constructed, and the improvement of the conductive performance is limited; when the amount of graphene is too much, due to the easy agglomeration of nanomaterials, the dispersion of graphene is difficult, which is not conducive to the improvement of the conductivity and mechanical properties of ceramics. Comparative Example 5 shows that TiB2 can be selected as the conductive phase. It has a high melting point, high chemical stability, high hardness, excellent wear resistance and good thermal conductivity, and has metal-like electronic conductivity and a positive temperature coefficient of resistivity. However, attention should be paid to the amount of TiB2. When the amount of TiB2 is too much, agglomeration may occur and cause abnormal growth of grains, resulting in reduced mechanical properties of ceramic composite materials.

[0151] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

[0152] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

Claims

1. A method for preparing a conductive ceramic material, characterized in that: The following steps are involved: (1) Weigh 70-80 parts of boron nitride powder, 13-16 parts of silicon carbide powder, 3-6 parts of titanium diboride powder, and 0.5-2 parts of graphene by weight; wherein the lateral size of the graphene is 1-10 μm; and the carbon-oxygen ratio is (30-50):1; (2) ultrasonically dispersing graphene in an alcohol solvent to obtain a graphene dispersion; (3) adding boron nitride powder, silicon carbide powder and titanium diboride powder to the graphene dispersion and stirring evenly to obtain a mixed solution; (4) ball-milling the mixed solution, drying it, and sieving it to obtain a mixed powder; (5) The mixed powder is placed in a hot press furnace and sintered to obtain a conductive ceramic material.

2. The method for preparing a conductive ceramic material according to claim 1, characterized in that: In step (1), the average particle size of the boron nitride powder is 0.5-1 μm, the average particle size of the silicon carbide powder is 0.5-1 μm, and the average particle size of the titanium diboride powder is 1-3 μm.

3. The method for preparing a conductive ceramic material according to claim 1, characterized in that: In step (1), the lateral size of graphene is 3-6 μm.

4. The method for preparing a conductive ceramic material according to claim 1, characterized in that: In step (2), the alcohol solvent is at least one of methanol, ethanol, propanol, ethylene glycol and propylene glycol.

5. The method for preparing a conductive ceramic material according to claim 1, characterized in that: The power of ultrasonic dispersion in step (2) is 100-200W.

6. The method for preparing a conductive ceramic material according to claim 1, characterized in that: The stirring rate in step (3) is 100-300 rpm.

7. The method for preparing a conductive ceramic material according to claim 1, characterized in that: In step (4), the ball-to-material ratio of the ball milling process is (4-6): 1, the ball milling speed is 200-400 rpm, and the ball milling time is 2-4 hours.

8. The method for preparing a conductive ceramic material according to claim 1, characterized in that: In step (5), the hot pressing pressure is 30-40 MPa; the sintering heating rate is 80-110°C / min, the sintering temperature is 1800-1950°C, and the sintering time is 1.5-2h.

9. A conductive ceramic material, characterized in that: The conductive ceramic material is prepared by the method for preparing the conductive ceramic material according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • High-strength high-toughness boron carbide-titanium boride-graphene composite ceramic and preparation method thereof

    CN112723889A

  • Titanium diboride-boron nitride-silicon carbide ceramic composite material prepared by hot pressed sintering and preparation method thereof

    CN113698210A

  • Ultra-high molecular weight polyethylene fiber spinning oil and preparation method thereof

    CN118563457A

  • ECO-friendly production of highly-conductive and clean graphene dispersions

    WO2015157280A1